Analysis of Leading Sectors Against Economic Growth in Merauke Regency 2016-2020 - Marthen A. I Nahumury; Fenty Y. Manuhutu (International Journal of Science and Society, 2022)
The purpose of this study was to determine the level of economic growth and the factors that influence the leading sector in Merauke Regency in 2016-2020. This study used a quantitative method using Location Quotiens (LQ) analysis tools and conducted research in Merauke Regency, to determine and find the leading sectors in 2016-2020. The results of my research show that there are several factors contained in the economic growth of nine sectors, there are 6 main base sectors in Merauke Regency in 2016-2020, namely agriculture, transportation, information and communication, finance, rental, corporate services, processing industry, services, trade, hotels, and restaurants. These six leading sectors will become the leading sectors for the non-base sector in order to be able to develop.